Unveiling the dynamics of rooftop solar entrepreneurship among micro-scale prosumers in Kerala - Ajith, N. K.; Velmurugan, V. P. (Edelweiss Applied Science and Technology, 2024)
The transition to sustainable energy sources is paramount in addressing global environmental challenges. Within this context, micro-scale solar prosumers, individuals who both consume and produce solar energy, play a pivotal role in decentralized energy production. This study investigates the multifaceted factors that impact the effectiveness of micro-scale solar prosumers in their engagement with and adoption of rooftop solar projects in Kerala. To achieve these objectives, a comprehensive research methodology is employed. The study encompasses a diverse sample of 240 respondents, representing various age groups, income levels, educational backgrounds, and genders. Data collection leverages surveys to gather insights into individuals’ attitudes, perceptions, and decisions regarding rooftop solar projects. The analysis utilizes a range of statistical techniques, including factor analysis, Cronbach’s alpha assessment, multiple regression, ANOVA, and correlation matrix analysis. These techniques enable a holistic exploration of the critical factors contributing to the effectiveness of micro-scale prosumers in solar initiatives. The findings of this study reveal significant insights. Government policies, subsidies, and incentives are identified as pivotal factors that significantly influence rooftop solar entrepreneurship. Additionally, technical considerations, such as solar resource availability and technological advancements, play a crucial role in shaping individuals’ decisions in this domain. Furthermore, the study underscores the importance of financial aspects, including incentives and financing options, in driving the adoption of solar projects among micro-scale prosumers.